Pengaruh Konsentrasi Dan Rasio Berat Few Layer Graphene (FLG) Terhadap Sifat Mekanis Aspal Beton Jenis Asphalt Treated Base (ATB) - Muhammad Sugandi; Amun Amri; Syelvia Putri Utami; Muhammad Shalahuddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Developing in highway is needed to produce better mechanical properties. This study aims to produce concrete asphalt by adding FLG (Few-Layer Graphene) from graphite, and then comparing the contribution of graphene with concentration and weight ratio of FLG to concrete asphalt as variations. Making asphalt concrete-FLG composite was started from making FLG with concentrations of 10, and 20 mg/ml using the turbulence-assisted shear exfoliation (TASE) method. Then, FLG was added to the bitumen with these variations and mixing it at 150 ᴼC and stirred for 10 minutes for homogenize. The homogenized asphalt bitumen was then mixed with the aggregates that have been prepared using a filter analyzer. The united bitumen and aggregates were then compacted using Marshall Automatic Compactor (MAC) with the number of collisions as much as 112 times and soaked in a water bath for 24 hours at 25 ᴼC. After 24 hours, the Marshall object test was weighed and soaked again for 30 minutes at 60 ᴼC before Marshall’s test. The results showed that for bitumen asphalt, the best penetration was exhibited by sample synthesized using FLG with concentrations of 20 mg/ml and 9% wt, namely 48.1 dmm. For Marshall’s test, the best flow value was also exhibited by the sample with FLG concentrations of 20 mg/ml and 9% wt, namely 4.3 mm. FTIR testing showed that there was an interaction between the FLG and bitumen in the double bond region and single bond stretch.Keywords : asphalt, few-layer graphene, flow, penetrations, softening point, stability